Genome Evolution 2003
DOI: 10.1007/978-94-010-0263-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Maximum likelihood methods for detecting adaptive evolution after gene duplication

Abstract: The rapid accumulation of genomic sequences in public databases will finally allow large scale studies of gene family evolution, including evaluation of the role of positive Darwinian selection following a duplication event. This will be possible because recent statistical methods of comparing synonymous and nonsynonymous substitution rates permit reliable detection of positive selection at individual amino acid sites and along evolutionary lineages. Here, we summarize maximum-likelihood based methods, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 45 publications
1
98
0
Order By: Relevance
“…Both these gene families have been well studied. Evidence has been found for the action of positive Darwinian selection since the divergence of ECP and EDN (Zhang et al 1998;Bielawski and Yang 2003) but not since the divergence of the e and c globins (G. Aguileta, pers. commun.).…”
Section: Discussionmentioning
confidence: 99%
“…Both these gene families have been well studied. Evidence has been found for the action of positive Darwinian selection since the divergence of ECP and EDN (Zhang et al 1998;Bielawski and Yang 2003) but not since the divergence of the e and c globins (G. Aguileta, pers. commun.).…”
Section: Discussionmentioning
confidence: 99%
“…1) were specified as foreground branches, thus allowing for different xÕs both over a subset of branches in the gene phylogeny and sites. This constraint has been used previously to test for positive selection following gene duplication (Bielawski and Yang 2003) and reflects a model of duplicate gene evolution whereby positive selection acts initially on duplicates followed by purifying selection in ancestral lineages (Hughes 1999). We used the modified branch-sites Model A of Zhang et al (2005) in order to avoid problems with an elevated type 1 error rate reported for older branch-sites models (Yang and Nielsen 2002), including a nested model with x 2 = 1 fixed (Model A null ).…”
Section: Codon Substitution Modelsmentioning
confidence: 99%
“…3, Table 2), consistent with strong purifying selection acting on duplicate copies. Second, a signature of positive selection is absent from branchsites models, which have increased power to detect adaptive evolution acting during discrete intervals of a geneÔs evolutionary history (Bielawski and Yang 2003). For the modified branch-sites Model A (Table 2), we specified the two branches immediately following the duplication of FLO or DEF (x 1 ) as foreground branches, and those prior to the duplication (x 0 ) as well as daughter branches (x 2 , x 3 ) as background branches (Fig.…”
Section: Mechanisms Of Duplicate Gene Preservationmentioning
confidence: 99%
See 2 more Smart Citations